Promoting the Use of Local Pasteurized Whole Milk in Contemporary Beverage Businesses in Padang, West Sumatra: Fostering Nutritional Awareness and Economic Growth - Ratni, Eli; Setyaka, Virtuous (Andalasian International Journal of Social and Entrepreneurial Development, 2023)
In regions like Padang and West Sumatra, where nutritional deficiencies and economic challenges persist, promoting local pasteurized whole milk in contemporary beverage businesses holds promise for fostering nutritional awareness and economic growth. This article describes the efficacy of educational initiatives to encourage local milk use among beverage businesses in Padang. Through a series of community engagement activities held in December 2022, ten coffee shops and business owners were educated on the benefits of utilizing locally produced pure milk in their beverage offerings. The study employs a three-stage approach encompassing preparation, implementation, and evaluation. Results indicate that local pasteurized milk enhances beverage quality, supports local farmers, and aligns with consumer preferences for fresher, ethically sourced ingredients. Moreover, promoting pasteurized milk contributes to a more sustainable and environmentally friendly beverage industry. The findings underscore the importance of promoting local milk products in fostering economic development and improving community well-being. Recommendations are provided for further study and program expansion to maximize the positive impact of such initiatives on local economies and public health